Investigation of working processes in a flowing channel of ramjet engine - Maslov E. A. Evgeny Anatolievich; Faraponov V. V.; Arkhipov V. A. Vladimir Afanasjevich; Zharova I. K. Irina Konstantinovna; Kozlov E. A. Evgeny Aleksandrovich; Savkina N. V. Nadezhda Valerjevna (2019, 2019)
Title screen